Potensi Small Business dalam Meningkatkan Perekonomian Masyarakat: Studi Kasus Usaha Minuman Nay -Nay Kota Medan - Salsa Zuhriana Nasution; Melissa Angelina Multi Silalahi; Emi Angelina Sinambela; Rifqi Fauzi; Dionisius Sihombing; Fadli Agus Triansyah (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to analyze the potential of micro, small, and medium enterprises (MSMEs) in enhancing the local economy through a case study of the Nay-Nay beverage business in Medan City. The research focuses on the contributions of MSMEs to job creation, income generation, improvement of purchasing power, development of local human resource skills, and the involvement of the local community in supply chain activities. A qualitative approach with a descriptive case study design was employed, utilizing semi-structured interviews, participant observation, and documentation analysis for data collection. The findings indicate that Nay-Nay plays a significant role in strengthening the local economic structure. The business creates employment opportunities for the surrounding community, increases household income, and contributes to the development of workforce competencies relevant to the food and beverage service industry. Moreover, the inclusion of local suppliers in the procurement of raw materials and distribution processes generates a multiplier effect that stimulates the local business ecosystem. Nonetheless, the enterprise faces notable challenges such as limited access to capital, price volatility of raw materials, and intense market competition. Overall, this study affirms that MSMEs are crucial drivers of inclusive and sustainable economic development and highlights the need for policy interventions that enhance managerial capacity and improve access to financing for small business actors.